A meta-analysis on the lifetime and period prevalence of self-injury among adolescents with depression - Wu, Yanli; Zhang, Yanhong; Wang, Chengzhen; Huang, Beibei (Frontiers in Public Health, 2024)
Background: Adolescents are vulnerable to mental disorders due to physiological, psychosocial, and cognitive changes during this critical developmental stage. Depression, in particular, can lead to high-risk behaviors such as self-injury (SI) and suicide. This study aims to estimate the pooled prevalence of SI behaviors among adolescents with depression.We systematically searched databases including EMBASE, Scopus, PubMed, and Web of Sciences for relevant articles published on adolescents with depression from January 1, 2000, to January 1, 2024. The quality assessment of the studies was conducted using the Joanna Briggs Institute (JBI) criteria. The global prevalence of SI was calculated based on a random effects model using Stata software version 17.Results: Our analysis included twenty-nine studies involving 12,934 adolescents. The lifetime prevalence of SI was 52% (95% Confidence Interval [CI]: 41-64), while the period prevalence was 57% (95% CI: 49-64). Notably, a significant relationship was observed between the prevalence of SI and the year of publication of articles (p=0.002). Furthermore, publication bias was not significant for both lifetime prevalence (P = 0.281) and period prevalence (0.358).The prevalence of self-injurious behaviors in adolescents with depression is alarmingly high, with more than half of adolescents having engaged in these high-risk behaviors during their lifetime or within the last year. Given the associated risk of suicide, it is crucial to identify individuals at risk and provide timely interventions.